Methodological Issues in Operationalising the Capability Approach in Empirical Research: an Example of Cross-Country Research on Youth Unemployment in the EU - Emma Hollywood; Valerie Egdell; Ronald McQuaid; Dirk Michel-Schertges (Social Work & Society, 2012)
This paper considers the experiences from nine in-depth case studies (undertaken as part of the "WorkAble" project) examining the transitions of (disadvantaged) young people: from compulsory school to further education; from education/vocational training to the labour market; and from unemployment/outside the labour market to employment.  It considers two key issues related to using the Capability Approach as a central conceptual guide in the design of in-depth qualitative research.  First, how to operationalise the Capability Approach in the methodology, an issue around which there is considerable debate in the literature in particular how to measure capabilities and which capabilities to measure.  Second, how to conduct research that is comparable, but is also adaptable to the particular social and institutional contexts of the nine different nations.  Specific issues related to the operationalisation of the Capability Approach, encountered when conducting the cross-country in-depth case studies, are highlighted; and debates from the capabilities literature discussed.